Level of cattle rearing practices followed by farmers of Indo-Gangetic plain zone - RAJEEV, RAJEEV; KUMAR, RAVINDER; SINGH, R; KUMAR, NEERAJ; KUMAR, PRAVEEN (The Indian Journal of Animal Sciences, 2016)
The sample of 90 respondents’ was collected for present study from Shamli district in Indo-Gangetic plain zone. Sugarcane tops were the main fodder crop from October to May months. The sugarcane tops were fed with mix of berseem or mustard cake or others concentrates from January to May. 31.11% respondents used wheat straw mixed with other green fodders followed by jowar, karbi, berseem and lobia as 27.77, 3.33, 2.22 and 2.22%, respectively. It was found that 28.80% animals were milch animal in study area. 38.88% of the respondents provided colostrums within 2 h of birth, 2–4 within hours and the placenta. It was also observed that 43.33% allowed suckling of their calf upto six months. However, 91.11% of the respondents did not dehorn calve. The adoption level regarding feeding practices of cow rearing was providing clean and fresh drinking water which have higher180 score (I rank) of feeding and lowest score was grazing which found only 17score (X ranks), followed 172, 103, 98, 96,102, 97, 69, and 47 score occupied the ranks III, IV, V, VI, VII, VIII and IX, respectively. Out of eight practices included in adoption of calf rearing management practices, Feeding of colostrum to newly born calves within 2 h after the birth was the highest score and occupied (Ist rank). The II and III ranks were occupied by attending newly born calf and proper cleaning of mucous from mouth and nostrils 139 score and trimming of hooves 94 score, respectively. Lighting and disinfection of naval cord, regular deworming of calves, right time method of dehorning and right time castration were VI, V, VI, VII, and VIII ranks, respectively. However, such types of practices are followed for sustainable livestock husbandry in this area since long time.